Variations in Serum CEA and CYFRA21-1 Levels Before and After Surgery Facilitate Prognosis of Non-small Cell Lung Cancer Patients - Xinchun DUAN (Chinese Journal of Lung Cancer, 2015)
Background and objective Serum carcinoembryonic antigen (CEA) and the soluble fragment of cytokeratin 19 (CYFRA21-1) are important tumor markers (TMs) in the preoperative examination of patients with non-small cell lung cancer (NSCLC). However, the prognostic role of these markers in NSCLC patients remains controversial. The aim of the study was to investigate the clinical significance of serum CEA variances and CYFRA21-1 levels for the prognosis of NSCLC patients following surgery. Methods This retrospective study investigated the clinical records and follow-up sessions of 175 patients with NSCLC who accepted surgery and adjuvant chemotherapy. Patients were subdivided into groups based on serum CEA and CYFRA21-1 levels. Survival analysis was conducted using Kaplan-Meier method for each group. The prognostic factor was evaluated using Cox proportional hazards model. Results The overall survival (OS) of patients with high preoperative CEA or CYFRA21-1 levels was lower than that of patients with normal preoperative CEA or CYFRA21-1 levels. The OS displayed a significant difference (P=0.001) between groups with high and normal preoperative CYFRA21-1. Compared with groups exhibiting normal preoperative and postoperative levels of CEA or CYFRA21-1, the OS was shorter for groups with high preoperative and postoperative levels of CEA or CYFRA21-1. The difference of the paired groups was significant (P<0.05). Compared with the groups with normal preoperative and postoperative levels of CEA and CYFRA21-1, the OS was lower for the groups with high preoperative and postoperative levels of CEA and CYFRA21-1, which indicated a significant difference (P<0.001). The CEACYFRA211 (HHHH), CEACYFRA211 (NNHH), CYFRA21-1 (HH), CEA (HH), and male gender were identified as independent prognostic factors (P<0.05). Conclusion This study suggested that the prognosis of NSCLC patients was not significantly satisfactory if preoperative and postoperative level of serum CEA or CYFRA21-1 was higher than standard value, especially if the preoperative and postoperative levels of CYFRA21-1 and CEA were higher than the standard values. The measurement of preoperative and postoperative levels of CYFRA21-1 and CEA proved helpful for the prognosis of patients with NSCLC.